Characterization of Urine-Derived Stromal/Stem Cells from Healthy Dogs and Dogs Affected by Chronic Kidney Disease (CKD) - Anna Lange-Consiglio; Filippo Tagliasacchi; Fausto Cremonesi; Claudia Gusmara; Claudia Pollera; Paola Scarpa; Giulia Gaspari; Pietro Riccaboni (Animals)
Urine-derived mesenchymal stromal/stem cells (USCs) could be a valuable source of cells in regenerative medicine because urine can be easily collected non-invasively. In this paper, USCs were isolated from both healthy dogs and dogs affected by chronic kidney disease (CKD), and the efficacy of collection methods (spontaneous micturition, bladder catheterization, and cystocentesis) were compared. Isolated cells were cultured in the presence of platelet-rich plasma and studied for their proliferative capacity (growth curve, doubling time, and colony forming unit), differentiation properties, expression of mesenchymal markers, and Klotho protein. Morphologically, all cells were elongated and fibroblast-like. USCs isolated from samples collected by spontaneous micturition and bladder catheterization failed to proliferate, whilst USCs obtained by cystocentesis showed a doubling time of 2.04 days in healthy dogs and 1.7 days in dogs with CKD (p < 0.05). Cells were able to differentiate into osteogenic, chondrogenic, and adipogenic lines, showed positive expression to mesenchymal/stem markers, negative expression to hematopoietic markers, and major histocompatibility complex (MHCII) antigen. Klotho protein expression was confirmed. This study confirmed that USCs from healthy and CKD dogs can act as stem cells, with those from sick dogs having greater proliferative ability with the potential for use as autologous therapies.